2012
DOI: 10.1039/c1cc15864c
|View full text |Cite
|
Sign up to set email alerts
|

A facile one-step synthesis of polymer supported rhodium nanoparticles in organic medium and their catalytic performance in the dehydrogenation of ammonia-borane

Abstract: A new type of supported rhodium nanoparticles were reproducibly prepared from N(2)H(4)BH(3) reduction of [Rh(μ-Cl)(1,5-cod)](2) without using any solid support and pre-treatment technique. Their characterization shows the formation of well dispersed rhodium(0) nanoparticles within the framework of a polyaminoborane based polymeric support. These new rhodium(0) nanoparticles were found to be the most active supported catalyst in the catalytic dehydrogenation of ammonia-borane in water at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…TEM analysis also revealed that metal nanoparticles were only located on the rGO nanosheets suggesting predominant interaction with the oxygen chemical groups at the surface of this 2D nanomaterial. HRTEM analysis revealed a highly crystalline feature for the Rh nanoparticles, with a crystalline spacing of 0.234 nm, which can be assigned to Rh(111) face (Karahan et al, 2012). Moreover, lattice fringes are easily visible at the nanocomposite edges due to folding or rolling of the rGO sheets.…”
Section: Preparation and Characterization Of The Transducer Nanomaterialsmentioning
confidence: 98%
“…TEM analysis also revealed that metal nanoparticles were only located on the rGO nanosheets suggesting predominant interaction with the oxygen chemical groups at the surface of this 2D nanomaterial. HRTEM analysis revealed a highly crystalline feature for the Rh nanoparticles, with a crystalline spacing of 0.234 nm, which can be assigned to Rh(111) face (Karahan et al, 2012). Moreover, lattice fringes are easily visible at the nanocomposite edges due to folding or rolling of the rGO sheets.…”
Section: Preparation and Characterization Of The Transducer Nanomaterialsmentioning
confidence: 98%
“…[1,2] due to the current interest in the hydrogen storage, which is still one of the key problems in the "Hydrogen Economy" [3][4][5]. Additionally, the importance of catalytic dehydrogenation of amine-borane adducts in the polymer synthesis [6,7], tandem dehydrogenation-hydrogenation [8,9], and transfer hydrogenation [10] has also made a prominent contribution to the progress in this field. Of particular importance are the results of recent studies [viii-x] revealing that amine-boranes can be used as easily transportable sources of hydrogen for the catalytic hydrogenation of C-C multiple bonds (1), which is one of the most important processes in the organic chemistry [11].…”
Section: Introductionmentioning
confidence: 97%
“…Although noble metal catalysts can achieve rapid hydrolytic dehydrogenation, the limited resources of noble metals restrict their practical applications . Alternatively, non‐noble metals have attracted more and more attention .…”
Section: Figurementioning
confidence: 99%
“…Although noble metal catalysts can achieve rapid hydrolytic dehydrogenation, the limited resources of noble metals restrict their practical applications. [11][12][13][14] Alternatively,n on-noble metals have attracted more and more attention. [15][16][17][18][19][20] Up to now,t he catalytic kinetics of H 2 generation,h owever,d on ot meet the needs of practical applications.…”
mentioning
confidence: 99%